Perception of Bali cattle farmers on the performance of Extensionist based on agroecosystems at Timor Island - Luis Marnisah; Jefirstson Richset Riwukore; Fellyanus Habaora; Asnath Maria Fuah; Luki Abdullah; Rudy Priyanto; Ahmad Yani; Bagus Priyo Purwanto (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
This research aims to determine the perception of farmers on the performance of Extensionist in the agroecosystems of pasture, agriculture, plantation, and forest at Timor Island, so that it can be information for improving the performance of extension workers who have an impact on repair the welfare of farmers. This research was conducted from January to December 2018. The research location was determined purposively representing the agroecosystem of pasture, agriculture, plantation and forest. The determination of respondents are 5-10% of the number of farmers in each agroecosystem that has > 10 Bali cattle. Data collection methods are done through observation, interviews, and documentation. Data processing method uses a Likert Scale, then analyzed decriptivelly. Indicators to measure the performance of livestock Extensionist based on Extensionist profile, materials and methods, procurement of activities, availability of teaching aids, and intensity of extension activities. The results showed that farmers' perceptions at agroecosystems of pasture, agriculture, plantation, and forest toward livestock extensionist in the category agreed that the existence of extensionist could be said well in aspects of Extensionist profile, materials and methods, and procurement of activities. This condition explains that Extensionist in carrying out his duties and functions in the field in accordance with existing standards, namely as a mediator, motivator, educator, communicator, facilitator, and assistance/visits. Nevertheless, it is very necessary to improve and repair the role of Extensionist related to competence so that it can influence farmers to be more productive in developing Bali cattle farming business them. Then Bali cattle farmers in the pasture agroecosystem with the highest value of the use of teaching aids by extensionist were 2 kinds (44,0%). Then the average farmers in agricultural agroecosystems with the highest value of the use of teaching aids by extensionist is 1 kind (40,2%). Next, the average of farmers in plantation agroecosystems with the highest value of using teaching aids by Extensionist are > 2 kinds (47,9%). While the average farmers in forest agroecosystems with the highest value of the use of teaching aids by Extensionist is 1 kind (>77,3%). While the intensity of extension activities during the past year shows that the average farmers in agroecosystems of pasture (70,7%), agriculture (59,8%), plantations (50,0%), and forests (68,2%) said more from 1 time.